Who is Allah?: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"Who is Allah?" explores the nature and attributes of Allah as the singular, all-powerful God in Islam. It emphasizes His qualities of mercy, justice, and oneness, highlighting the significance of faith and worship in the lives of believers.